Lipoprotein apheresis efficacy, challenges and outcomes: A descriptive analysis from the UK Lipoprotein Apheresis Registry, 1989–2017. (November 2019) - Pottle, Alison; Thompson, Gilbert; Barbir, Mahmoud; Bayly, Graham; Cegla, Jaimini; Cramb, Robert; Dawson, Tina; Eatough, Ruth; Kale, Vaishali; Neuwirth, Clare; Nicholson, Kirsty; Payne, Jules; et al.
Abstract: Background and aims: In 2008, the National Institute of Health and Care Excellence in the UK recommended that patients undergoing lipoprotein apheresis (LA) should be included in an anonymised registry. The UK Lipoprotein Apheresis Registry was subsequently established in 2011. Methods: Between 2011 and 2017, data was entered retrospectively and prospectively by seven LA centres in the UK for 151 patients. Twenty-two patients were involved in a research study and were therefore excluded from the analysis. Observational data was analysed for the remaining 129 patients. Results: Most patients had heterozygous familial hypercholesterolaemia (HeFH) (45.0%); 23.3% had homozygous FH (HoFH); 7.8% had hyper-lipoproteinaemia (a) (Lp(a)) and 24.0% had other forms of dyslipidaemia. Detailed treatment data is available for 63 patients relating to 348 years of LA treatment. The number of years of treatment per patient ranged from 1 to 15. The mean reduction in interval mean LDL-C from the pre-procedure baseline was 43.14%. The mean reduction in interval mean Lp(a) from baseline was 37.95%. The registry data also shows a 62.5% reduction in major adverse cardiovascular events (MACE) between the 2 years prior to, and the first 2 years following introduction of LA. Conclusions: The data generated by the UK Lipoprotein Apheresis Registry demonstrates that LA is a very efficient method of reducing LDL-C and Lp(a) and lowers the incidence rate of MACE. LA is an important tool in the management of selected patients with HoFH and drug-resistant dyslipidaemias. Graphical abstract: Image 1 Highlights: The UK Lipoprotein Apheresis (LA) Registry was established in 2011. Between 2011 and 2017 data was entered retrospectively and prospectively by seven LA centres in the UK for 151 patients. The mean reduction in interval mean LDL-C from the pre-procedure baseline was 43.14% and 37.95% for Lp(a). There was a 62.5% reduction in major adverse cardiovascular events (MACE) following introduction of LA.